2021
DOI: 10.1021/acs.jpcc.1c00874
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Fast Thermal Dynamics at the Nanoscale through Frequency Domain Photoinduced Force Microscopy

Abstract: In illuminated tip–sample junctions, the absorption of light by the sample is accompanied by local heating and subsequent thermal expansion of the material. In photoinduced force microscopy (PiFM) experiments, thermal expansion is expected to affect the measured photoinduced force through the thermally modulated van der Waals force. Evidence for such thermal contributions in PiFM measurements has been demonstrated in the mid-infrared range, where the primary excitations are molecular vibrational modes. For PiF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Our results show that careful choice of detection method has to be made for optimal sensing of the photothermal signal induced by a short pulse excitation. While the same level of SNR improvement may be achieved by using other advanced demodulation techniques that are capable of capturing those high-frequency photothermal signals, such as signal synthesis using lock-in multi-channel demodulation 48 , 49 or boxcar averaging 50 , those advanced demodulation methods are not yet widely available. In contrast, the broadband detector and digitizer or MHz are readily available and highly cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that careful choice of detection method has to be made for optimal sensing of the photothermal signal induced by a short pulse excitation. While the same level of SNR improvement may be achieved by using other advanced demodulation techniques that are capable of capturing those high-frequency photothermal signals, such as signal synthesis using lock-in multi-channel demodulation 48 , 49 or boxcar averaging 50 , those advanced demodulation methods are not yet widely available. In contrast, the broadband detector and digitizer or MHz are readily available and highly cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…To verify our hypothesis, IR PiFM was applied to analyze the surface chemistry of ETFE-0 and ETFE-3 membranes at the nano-layer level. The IR PiFM technique has been reported to resolve vibrational signals between a probing tip and material surface [ 20 , 21 , 22 ], obtaining infrared spectroscopy results with a resolution up to the nanometer level [ 23 ]. Taking ETFE-0 as an example, the nano-level infrared spectra of the membrane surface obtained by IR PiFM ( Figure 4 a) showed that a C–H deformation vibration peak at 1453 cm −1 and C–F peak at 950–1400 cm −1 , which are consistent with the results obtained in ATR-FTIR ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…Jahng et al 's model 33 considered incident light causing a thermal expansion at the tip/sample junction and generating a force interaction through two processes: a “direct” contribution resulting from far-field transmission and absorption by the sample and an “indirect” contribution caused by the enhanced near field, generated by the antenna effect of the tip. The model indicated that the thermally stimulated forces would be as much as a hundred times stronger than the induced dipole force for most organic materials for mid infrared radiation and recent experimental data, utilising an innovative frequency domain force detection method that allows sub-μs time measurements, 34 suggests the same is true in the visible/near infrared region where energy transfer is through electronic excitations.…”
Section: The Origin Of Spectroscopic Contrast In Pifmmentioning
confidence: 91%
“…27,28 The resulting gradient force, F g , depends upon the polarisation of the particle in the z direction and because of its 1 Z 4 dependence, is highly localised that can be measured with very high spatial resolution. [29][30][31] Subsequently, experimental evidence accumulated that the cantilever response was dominated by dissipative effects rather than the dispersive response predicted by the dipole-dipole force model, 33,34 thus indicating the involvement of a thermal process in generating PiFM contrast. Jahng et al's model 33 considered incident light causing a thermal expansion at the tip/sample junction and generating a force interaction through two processes: a ''direct'' contribution resulting from far-field transmission and absorption by the sample and an ''indirect'' contribution caused by the enhanced near field, generated by the antenna effect of the tip.…”
Section: The Origin Of Spectroscopic Contrast In Pifmmentioning
confidence: 99%